Pengelolaan rekod keluarga masyarakat Kampung Cikurutug Elos di era digital - Lukman, Lukman; Rizal, Edwin; Perdana, Fitri (Jurnal Informatio, 2024)
The phenomena of document theft and misuse represent recurring issues in various contexts. Data misuse is defined as the unauthorized or illegal utilization of personal information, resulting in material and administrative losses. Given the significance of archives, effective management of personal and family records is essential, including the implementation of digitization as a security strategy, similar to archival management practices applied in formal institutions. This study focuses on the management of family records in the rural community of Kampung Cikurutug Elos, Cicurug-Sukabumi. The research aims to evaluate the level of community understanding in managing family documents through the perspective of the records life cycle. The methodology employed is qualitative descriptive, with data collection techniques encompassing observation, interviews, documentation, and literature review. Data analysis is conducted through stages of data reduction, data presentation, and conclusion drawing. Research findings indicate that the process of record creation and receipt stems from both formal and informal activities. Family members utilize these records for personal and collective interests. Organization and classification of records are performed based on family needs, with the use of storage equipment such as folders and the determination of strategic storage locations. Documents that have lost their utility are destroyed to prevent accumulation. Some residents have adopted digitization practices through digital photography and scanning. The study concludes that the community of Kampung Cikurutug Elos has implemented family record management with considerable effectiveness, as evidenced by the ease and speed of information retrieval processes.